Circulating microRNAs: potential biomarkers for common malignancies. (February 2015) - Khoury, Samantha; Tran, Nham
MicroRNAs (miRNAs) belong to a class of small noncoding RNAs (ncRNAs), which regulate gene expression at the post-transcriptional level. They are approximately 22 nucleotide sequences in length and have been predicted to control expression of up to 30–60% of all protein-coding genes in mammals. Considering this wide involvement in gene control, aberrant miRNA expression has a strong association with the presence and progression of a disease, hence generating much anticipation in using miRNAs as biomarkers for the diagnosis and prognosis of human cancers. The majority of these miRNAs are intracellular, but recently they have been discovered in bodily fluids. This review will provide an insight into these circulatory miRNA molecules and discuss their potential as cancer biomarkers.